Circular RNAs Are the Predominant Transcript Isoform from Hundreds of Human Genes in Diverse Cell Types - Salzman, Julia; Gawad, Charles; Wang, Peter Lincoln; Lacayo, Norman; Brown, Patrick O. (PLOS ONE, 2012)
Most human pre-mRNAs are spliced into linear molecules that retain the exon order defined by the genomic sequence. By deep sequencing of RNA from a variety of normal and malignant human cells, we found RNA transcripts from many human genes in which the exons were arranged in a non-canonical order. Statistical estimates and biochemical assays provided strong evidence that a substantial fraction of the spliced transcripts from hundreds of genes are circular RNAs. Our results suggest that a non-canonical mode of RNA splicing, resulting in a circular RNA isoform, is a general feature of the gene expression program in human cells.